Red Cell Genotyping by Multiplex PCR Identifies Antigen-Matched Blood Units for Transfusion-Dependent Thai Patients - Kamphon Intharanut (2018)
© 2017 S. Karger GmbH, Freiburg. Background: Antigen-negative red cell transfusion is required for transfusion-dependent patients. We developed multiplex PCR for red cell genotyping and calculated the possibility of finding compatible predicted phenotypes in Thai blood donor populations according to red cell alloantibodies found among Thai patients. Methods: 600 DNA samples obtained from unrelated healthy central and northern Thai blood donors were tested with the newly developed multiplex PCR for FY∗A, FY∗B, JK∗A, JK∗B, RHCE∗e, RHCE∗E, DI∗A and GYP∗Hut, GYP∗Mur, GYP∗Hop, GYP∗Bun, and GYP∗HF allele detections. Additionally, the possibility of finding compatible predicted phenotypes in two Thai blood donor populations was calculated to estimate the minimal number of tests needed to provide compatible blood. Results: The validity of multiplex PCR using known DNA controls and the phenotyping and genotyping results obtained by serological and PCR-SSP techniques were in agreement. The possibility of finding at least one compatible blood unit for patients with multiple antibodies was comparable in Thai populations. Conclusions: The multiplex PCR for red cell genotyping simultaneously interprets 7 alleles and 1 hybrid GP group. Similar strategies can be applied in other populations depending on alloantibody frequencies in transfusion-dependent patients, especially in a country with limited resources.